2018
DOI: 10.3389/fimmu.2018.02570
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mucocutaneous Candidiasis in Autoimmune Polyendocrine Syndrome Type 1

Abstract: Autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) is an autosomal recessive disease caused by mutations in the autoimmune regulator (AIRE) gene, characterized by the clinical triad of chronic mucocutaneous candidiasis (CMC), hypoparathyroidism, and adrenal insufficiency. CMC can be complicated by systemic candidiasis or oral squamous cell carcinoma (SCC), and may lead to death. The role of chronic Candida infection in the etiopathogenesis of oral SCC is unclear. Long-term use of fluconazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 107 publications
(155 reference statements)
1
42
0
2
Order By: Relevance
“…Chronic mucocutaneous candidiasis syndromes represent a group of several very rare heterogeneous immunologic disorders characterized by underlying immune deficiencies. Clinically, affected patients suffer from chronic and sometimes life-long persistent or recurrent mucocutaneous candidiasis involving the skin, nails, and genital mucosa; however, greater than 90% of patients present with oral involvement [80,81]. It is thought that the severity of the clinical manifestation correlates with the severity of the underlying immune defect.…”
Section: Chronic Mucocutaneous Candidiasis Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic mucocutaneous candidiasis syndromes represent a group of several very rare heterogeneous immunologic disorders characterized by underlying immune deficiencies. Clinically, affected patients suffer from chronic and sometimes life-long persistent or recurrent mucocutaneous candidiasis involving the skin, nails, and genital mucosa; however, greater than 90% of patients present with oral involvement [80,81]. It is thought that the severity of the clinical manifestation correlates with the severity of the underlying immune defect.…”
Section: Chronic Mucocutaneous Candidiasis Syndromesmentioning
confidence: 99%
“…It is thought that the severity of the clinical manifestation correlates with the severity of the underlying immune defect. Many types of chronic mucocutaneous candidiasis syndromes exist that include the sporadic form, forms secondary to immunosuppressive therapies, diabetes, T-cell deficiency or HIV infection, inherited familial genetic forms, and autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) [80,81]. These patients are often refractory to standard antifungal therapies and have an increased susceptibility to developing oral squamous cell carcinoma [70,81].…”
Section: Chronic Mucocutaneous Candidiasis Syndromesmentioning
confidence: 99%
“…Furthermore, patients with autosomal recessive autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) have mutations in the autoimmune regulator ( AIRE ) gene [87], resulting in a loss-of-function phenotype that causes the production of neutralizing autoantibodies against important cytokines with antifungal properties such as IL-17E, IL-17F, and IL-22 [88]. Autoantibodies against IL-22 and IL-17F are more common in APECED patients with CMC than in those without CMC, suggesting that type Th17 cytokines are central in human epithelial immunity against C. albicans infection [89,90]. However, recent experimental data have shown that autoantibodies against murine IL-17A do not increase susceptibility to OPC, while anti-IL-22 antibodies derived from patients increase the oral fungal burden [91].…”
Section: Barrier Sites In the Human Bodymentioning
confidence: 99%
“…Three types are described in the literature: type 1 (juvenile type), type 2 (adult type), and type 3 (the rarest). APS-1 is also known as Whitaker syndrome and autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) [ 2 ]. It is a very rare disorder inherited in a sporadic autosomal recessive pattern and caused by genetic mutations affecting the autoimmune regulator (AIRE) gene on chromosome 21 [ 2 , 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune polyglandular syndrome type 1 (APS-1) is defined by the coexistence of at least 2 of 3 major component diseases: chronic mucocutaneous candidiasis, autoimmune adrenal insufficiency, and primary hypoparathyroidism, or only 1 if a sibling has the disease [ 1 3 ]. The syndrome is a rare disorder with an autosomal recessive inheritance pattern [ 1 , 2 , 4 , 5 ]. Vascular calcification is a rare manifestation of the syndrome [ 6 ], and it can be severe, causing significant lesions and ischemia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%